Elizabeth Hoover, The River Is in Us: Fighting Toxics in a Mohawk Community. Issue Volume 15(2021)Special Issue (31st March 2021) - Arnold, Philip
Abstract : Elizabeth Hoover, The River Is in Us: Fighting Toxics in a Mohawk Community (Minneapolis: University of Minnesota Press, 2017), 392 pp., $112.00 (cloth), ISBN: 978- 1-5179-0302-2.